Durability and tolerability of dapagliflozin over 52 weeks as add‐on to metformin and sulphonylurea in type 2 diabetes. Issue 11 (4th September 2015) - Matthaei, S.; Bowering, K.; Rohwedder, K.; Sugg, J.; Parikh, S.; Johnsson, E.; on behalf of the Study 05 Group
<x xml:space="preserve">Abstract</x> Aims To evaluate the safety and efficacy of dapagliflozin as add‐on therapy to metformin plus sulphonylurea over 52 weeks. Methods Patients with type 2 diabetes mellitus (T2DM) using sulphonylurea and metformin received dapagliflozin 10 mg/day or placebo added to therapy for 52 weeks (24‐week randomized, double‐blind period plus 28‐week double‐blind extension). Results A total of 219 patients were randomized 1 : 1 to dapagliflozin or placebo. Over 52 weeks, glycated haemoglobin (HbA1c) and fasting plasma glucose levels showed greater improvement from baseline with dapagliflozin (−0.8% and −1.5 mmol/l) than with placebo (−0.1% and 0.6 mmol/l). More patients achieved HbA1c <7.0% with dapagliflozin (27.3%) than with placebo (11.3%) at 52 weeks. Dapagliflozin was associated with greater reductions in body weight and systolic blood pressure (−2.9 kg and −1.0 mmHg) compared with placebo (−1.0 kg and 1.1 mmHg). Greater increases in total, LDL and HDL cholesterol and decreases in triglycerides were observed with dapagliflozin (3.4, 4.8, 6.9 and −8.0%, respectively) versus placebo (1.4, 0.9, 0.6 and 2.9%, respectively). Fewer patients were rescued for failing to reach glycaemic targets with dapagliflozin (9.3%) than with placebo (44.4%). Adverse events and serious adverse events were similar between groups (dapagliflozin: 69.7 and 6.4%; placebo: 73.4 and 7.3%). More hypoglycaemic events were observed with dapagliflozin (15.6%) than with placebo (8.3%). Genital infections were reported in more patients in the dapagliflozin (10.1%) than in the placebo group (0.9%) and urinary tract infection frequency was similar in the two groups (10.1 and 11.0%). Conclusion Dapagliflozin as add‐on to metformin plus a sulphonylurea was well tolerated and improvement in glycaemic control was maintained over 52 weeks.